Bottom‐up proteomics of envelope proteins extracted from spinach chloroplast via high organic content CE‐MS. Issue 5 (19th February 2020) - Cheng, Jianhui; Morin, Gregg B.; Chen, David D. Y.
Abstract: A high organic content CE‐MS/MS (HOCE‐MS/MS) method was developed for the proteomic analysis of envelope proteins extracted from spinach leaves. Separation was performed in a 1‐m long hydroxypropyl cellulose coated capillary, using 8% (v/v) formic acid in 70% (v/v) methanol and 22% water as the BGE. A flow‐through microvial interface was used to couple the CE system with an Orbitrap Fusion Lumos mass spectrometer, and field‐amplified sample stacking was used to improve the concentration sensitivity. Using this optimized method, 3579 peptides and 1141 proteins were identified using the Proteome Discoverer software with a 1% false discovery rate at the protein level. Relative to conventional aqueous CE, HOCE‐MS did a better job of discovering hydrophobic peptides and provided more peptide and protein identifications. Relative to nano‐LC‐MS, it achieved comparable peptide and protein identification performance and detected peptides not identified by LC‐MS: of the full set of peptides identified using the two techniques, 19% were identified only using HOCE‐MS. It also outperformed nano‐LC‐MS with respect to the detection of low molecular weight peptides.